Dual-factor model of sleep and diet: a new approach to understanding central fatigue - Zhang, Yifei; Zhang, Zehan; Yu, Qingqian; Lan, Bijuan; Shi, Qinghuan; Liu, Yan; Zhang, Weiyue; Li, Feng (Frontiers in Neuroscience, 2024)
BackgroundNumerous studies have recently examined the impact of dietary factors such as high-fat diets on fatigue. Our study aims to investigate whether high-fat diet (HFD) alone or combined with alternate-day fasting (ADF) can lead to the central fatigue symptoms and to investigate the potential integration of dietary and sleep variables in the development of central fatigue models.MethodsSeventy-five male Wistar rats were divided into five groups: control, HFD, HFD + ADF, modified multiple platform method (MMPM), and MMPM+HFD + ADF. Each group underwent a 21-day modeling period according to their respective protocol. Their behavioral characteristics, fatigue biochemical markers, hippocampal pathological changes, mitochondrial ultrastructure, and oxidative stress damage were analyzed.ResultsOur findings demonstrate that using only HFD did not cause central fatigue, but combining it with ADF did. This combination led to reduced exercise endurance, decreased locomotor activity, impaired learning and memory abilities, along with alterations in serum levels of alanine aminotransferase (ALT), creatine kinase (CK), and lactate (LAC), as well as hippocampal pathological damage and other central fatigue symptoms. Moreover, the MMPM+HFD + ADF method led to the most obvious central fatigue symptoms in rats, including a variety of behavioral changes, alterations in fatigue-related biochemical metabolic markers, prominent pathological changes in hippocampal tissue, severe damage to the ultrastructure of mitochondria in hippocampal regions, changes in neurotransmitters, and evident oxidative stress damage. Additionally, it was observed that rats subjected to HFD + ADF, MMPM, and MMPM+HFD + ADF modeling method exhibited significant brain oxidative stress damage.ConclusionWe have demonstrated the promotive role of dietary factors in the development of central fatigue and have successfully established a more stable and clinically relevant animal model of central fatigue by integrating dietary and sleep factors.